2010
DOI: 10.1016/j.snb.2009.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Drift compensation of gas sensor array data by common principal component analysis

Abstract: A new drift compensation method based on Common Principal Component Analysis (CPCA) is proposed. The drift variance in data is found as the principal components computed by CPCA. This method finds components that are common for all gasses in feature space. The method is compared in classification task with respect to the other approaches published where the drift direction is estimated through a Principal Component Analysis (PCA) of a reference gas. The proposed new method -employing no specific reference gas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(88 citation statements)
references
References 14 publications
0
88
0
Order By: Relevance
“…The cluster centers were used as a basis to define a FIS which was subsequently used to explore and understand environmental patterns over the years. Set 1 data is used in the Wavelet -FCM -FIS based initial water data understanding and modelling where as Set 2 and Set 3 are used to measure the sensory drift over the years and to test prediction performance of the system [10][11][12][13].…”
Section: Data and Systemmentioning
confidence: 99%
“…The cluster centers were used as a basis to define a FIS which was subsequently used to explore and understand environmental patterns over the years. Set 1 data is used in the Wavelet -FCM -FIS based initial water data understanding and modelling where as Set 2 and Set 3 are used to measure the sensory drift over the years and to test prediction performance of the system [10][11][12][13].…”
Section: Data and Systemmentioning
confidence: 99%
“…Among the above-mentioned methods, discrete wavelet transform is more flexible because it can analyze the signal at different frequency bands with different resolutions. In case of E-nose measurements, since the drift effects are correlated, the multivariate methods allow capturing more information from all the sensors permitting modeling more complex or nonlinear drift effects [12]. In the literature around the E-nose research different multivariate methods can be found.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the second idea is collecting drift trace from the former testing process. The common methods used for extracting drift signals include Principal Component Analysis (PCA), (6)(7)(8) Independent Component Analysis (ICA), (9) and Partial Least-Squares (PLS). (10) Aside from these methods, the Orthogonal Signal Correction (OSC) is superior to drift correction as shown in a recent study by Padilla et al (11) Generally speaking, all the component correction methods aim to find one preferable direction to eliminate drift.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Aside from these methods, the Orthogonal Signal Correction (OSC) is superior to drift correction as shown in a recent study by Padilla et al (11) Generally speaking, all the component correction methods aim to find one preferable direction to eliminate drift. However, the drift direction varies with time and gas type in the mapping space, (6) and consecutive groups of samples are needed for predicting each drift direction. Thus, a great deal of calculation is performed during the testing process.…”
Section: Introductionmentioning
confidence: 99%